UNRAVELING THE ENVIRONMENTAL FOOTPRINT OF PLASTICS AND CHEMICALS ON MARINE FOOD NETWORKS - Iskandar Tuasamu; Ikbal Nurullah Fajar; Sigit Sugiardi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The increasing accumulation of plastics and chemical pollutants in marine ecosystems has become a critical environmental concern, threatening biodiversity, food web stability, and human health. Plastics, particularly microplastics and nanoplastics, not only persist in the environment but also act as vectors for toxic chemical compounds such as persistent organic pollutants (POPs), heavy metals, and per- and polyfluoroalkyl substances (PFAS). This study aims to unravel the combined environmental footprint of plastics and associated chemicals on marine food networks by synthesizing findings from recent empirical and modeling studies. A systematic literature review (SLR) was conducted using Scopus, ScienceDirect, SpringerLink, and MDPI databases, covering publications from 2015 to 2025. Forty-two peer-reviewed articles were selected based on PRISMA 2020 guidelines, focusing on topics related to microplastic contamination, chemical pollutant interactions, bioaccumulation, and trophic transfer. Data were analyzed through descriptive and thematic analysis, identifying key pathways, ecological impacts, and knowledge gaps. Findings reveal that microplastics facilitate the adsorption and transport of chemical pollutants through ingestion and trophic transfer, leading to bioaccumulation and, in some cases, biomagnification across trophic levels. Combined exposure induces oxidative stress, endocrine disruption, growth inhibition, and reproductive failure in marine organisms. These synergistic effects disrupt food web dynamics, reduce biomass, and pose emerging risks to seafood safety and human health. The review also identifies critical knowledge gaps in multipollutant interactions, long-term field studies, and integrated modeling approaches. This study emphasizes the need for multidisciplinary research, evidence-based policies, and integrated management strategies to mitigate the dual threats of plastic and chemical pollution. Strengthening global collaboration, enforcing stricter regulations on plastic additives, improving waste management systems, and promoting ocean monitoring programs are essential for safeguarding marine ecosystems and achieving Sustainable Development Goals (SDGs), particularly SDG 14 (Life Below Water) and SDG 3 (Good Health and Well-being).